Applicability of a Novel Formula (Bogossian formula) for Evaluation of the QT‐Interval in Heart Failure and Left Bundle Branch Block Due to Right Ventricular Pacing. Issue 4 (3rd March 2017) - FROMMEYER, GERRIT; BOGOSSIAN, HARILAOS; PECHLIVANIDOU, ELENI; CONZEN, PHILIPP; GEMEIN, CHRISTOPHER; WEIPERT, KAY; HELMIG, INGA; CHASAN, RITVAN; JOHNSON, VICTORIA; ECKARDT, LARS; HAMM, CHRISTIAN W; SEYFARTH, MELCHIOR; et al.
Abstract : Background: The presence of left bundle branch block (LBBB) due to right ventricular pacing represents a particular challenge in properly measuring the QTc interval. In 2014, a new formula for the evaluation of QT interval in patients with LBBB was reported. Methods: 145 patients with implantable cardioverter defibrillator were included in this prospective multicenter observational study. Inclusion criteria were: no permanent right ventricular stimulation, an intrinsic QRS interval of <120 ms, and reduced left ventricular function. 12‐lead electrocardiogram recordings during intrinsic rhythm and during right ventricular threshold testing were performed. After LBBB correction using the reported Bogossian formula, the QTc interval was evaluated with Bazett's formula. The corrected QTc interval was compared in each patient with the QTc interval during intrinsic rhythm. All measurements were performed by an experienced electrophysiologist and a trainee who worked independently and in a blinded manner. Results: 74 patients (65 ± 13 years; male n = 42) with apical and 71 patients (68 ± 11 years; male n = 42) with nonapical right ventricular pacing were included in this study. The mean left ventricular ejection fraction was 40 ± 13%. The QTc interval was determined to be 461 ± 34 ms (modified by Bogossian's formula) in paced and 436 ± 34 ms in intrinsic rhythm. The QTc interval was overestimated by ΔQTc of 25 ± 21 ms (mean deviation 5.7%) when using the Bogossian formula. Conclusion: The novel Bogossian formula seems to be a reliable tool for QTc interval evaluation in patients with heart failure and right ventricular pacing. However, a slight overestimation of the QT‐interval must be respected.